IN SILICO ANALYSIS OF ACTIVE LIGANDS OF MITRAGYNA SPECIOSA KORTH PLANT AS ANTICOCEPTIVE: ANALISIS IN SILICO LIGAND AKTIF TANAMAN MITRAGYNA SPECIOSA KORTH SEBAGAI ANTIOSISEPTIF - Donor Utomo Muhammad Susilo; Dodi Iskandar; Mhd Syamsu Bahri (PT. ROCE WISDOM ACEH, 2025)
Mitragyna speciosa Korth (MSK) plant or known as Kratom is a leading export commodity from West Kalimantan Province. The leaves of this plant are processed by farmers into crumbs and flour to be sold to collectors and exported abroad, especially to the United States. The leaves of this plant have long been used by local people as a traditional herbal medicine to relieve pain and provide a calming effect if the boiled water is drunk. The purpose of this study was to evaluate the content of Kratom as an Antinociceptive, Analgesic, General Anesthetic, Vasodilator, and 5 Hydroxytryptamine Release Stimulant (5HRS). Active metabolites and most of the simplified molecular input line entry (SMILE) codes of the MSK plant were obtained from the Knapsack database. The relationship between active metabolites and proteins in the human body was analyzed using STITCH software computationally. There are 23 active metabolites in MSK leaves. Isomitraphylline, Isopaynantheine, and Paynantheine have the highest Antinociceptive bioactivity (82.8). Corynoxine and Corynoxine B have higher Analgesic bioactivity (81.5) compared to other ligands. Isomitrafoline and Speciophylline show the strongest general Anesthetic (92.2) compared to other ligands.